IL-1β, But Not Programed Death-1 and Programed Death Ligand Pathway, Is Critical for the Human Th17 Response to Mycobacterium tuberculosis - Stephen-Victor, Emmanuel; Sharma, Varun Kumar; Das, Mrinmoy; Karnam, Anupama; Saha, Chaitrali; Lecerf, Maxime; Galeotti, Caroline; Kaveri, Srinivas V.; Bayry, Jagadeesh (Frontiers in Immunology, 2016)
The programmed death-1 (PD-1)- programmed death ligand-1 (PD-L1) and PD-L2 co-inhibitory pathway has been implicated in the evasion strategies of Mycobacterium tuberculosis. Specifically, M. tuberculosis-induced PD-L1 orchestrates expansion of regulatory T cells (Tregs) and suppression of Th1 response. However, the role of PD pathway in regulating Th17 response to M. tuberculosis has not been investigated. In the present report, we demonstrate that M. tuberculosis and M. tuberculosis-derived antigen fractions have differential abilities to mediate human monocyte and dendritic cell (DC)-mediated Th17 response and were independent of expression of PD-L1 or PD-L2 on aforementioned antigen-presenting cells. Importantly, we observed that blockade of PD-L1 or PD-1 did not significantly modify either the frequencies of Th17 cells or the production of IL-17 from CD4+ T cells though IFN-γ response was significantly enhanced. On the contrary, IL-1β from monocytes and DCs were critical for the Th17 response to M. tuberculosis. Together, our results indicate that IL-1β but not members of the programmed death pathway is critical for human Th17 response to M. tuberculosis